Analisis Parameter Fisika Kimia Air di Danau Buatan Perumnas Griya Martubung Kota Medan (Parameter Analysis of Physics and Chemical Water on Artificial Lake Perumnas Griya Martubung, Medan City) - Frandy Tulus Siahaan; Hesti Wahyuningsih; Zulham Apandy Harahap (AQUACOASTMARINE, 2017)
The research about parameter analysis of physics and chemistry is one way to know of water quality and the value contained in the water bodies. The aim of this research paper is to learn the value of physics and chemistry content on the water and status water quality based on regulations PP 82 year 2001 in Artificial Lake Perumnas Griya Martubung, Medan City. The research done by using porpusive sampling method. Determination of water quality status on the lake using STORET method and table of water quality standard from regulations PP 82 year 2001. The measurement result shows that the physical and chemical parameter of water that isn’t pass the quality standard was temperature (32.33°C); brightness (15-18 cm); TSS/Total Suspended Solid (256 to 188 mg/L); the degree of acidity/pH (6.5 mg/L); nitrate/NO3-N (0.2 to 0.36 mg/L); phosphate/P (0.81 to 1 mg/L) and which parameter passed of quality standard is Dissolved oxygen/DO (0.26 to 0.36 mg/L); Biochemical Oxygen Demand/BOD (17 to 18.75 mg/L); total ammonia / NH3-N (8.5 to 8.9 mg/L); and oils and fats (4.5 to 8.5 mg/L). Quality status of water Artificial Lake in Griya Martubung Housing was heavily polluted for standard quality on class III water.Keywords: Artificial Lake Perumnas Griya Martubung, Water Quality, method STORET